HER2 expression and mismatch repair status in endometrial clear cell carcinoma - Yılmaz Erözbek, Sıla; Bayramoğlu, Zeynep; Özdemir, İsa Aykut; Ülker, Volkan; Müezzinoğlu, Bahar (Springer, 2022)
[Abstract Not Available]
Keywords: HER2; Endometrial; Clear Cell Carcinoma